Answer:
f(g) = -3( x^2 -x-6) -6 = -3x^2+3x+12
<em>Hey There!!</em>
<em>The answer is below!!</em>
Step-by-step explanation:
We move all terms to the left:
![-6n+22-(-4n+14-10n+22)=0](https://tex.z-dn.net/?f=-6n%2B22-%28-4n%2B14-10n%2B22%29%3D0)
We add all the numbers together, and all the variables
![-6n-(-14n+36)+22=0](https://tex.z-dn.net/?f=-6n-%28-14n%2B36%29%2B22%3D0)
We get rid of parentheses
![-6n+14n-36+22=0](https://tex.z-dn.net/?f=-6n%2B14n-36%2B22%3D0)
After that, We add all the numbers together, and all the variables
![8n-14=0](https://tex.z-dn.net/?f=8n-14%3D0)
Then, We move all terms containing n to the left, all other terms to the right
![8n=14](https://tex.z-dn.net/?f=8n%3D14)
![n=14/8](https://tex.z-dn.net/?f=n%3D14%2F8)
![n=1+3/4](https://tex.z-dn.net/?f=n%3D1%2B3%2F4)
<em>I don't know this is </em>
% right....
![So.....GoodLuck!!](https://tex.z-dn.net/?f=So.....GoodLuck%21%21)
#
![Bold](https://tex.z-dn.net/?f=Bold)
#
![Brainly!](https://tex.z-dn.net/?f=Brainly%21)
![_{Loserbrazts}](https://tex.z-dn.net/?f=_%7BLoserbrazts%7D)
Ok can you please show the formula or give more information please